The effect of body percussion on balance and coordination in elderly people - Girgin, Nuray; Algun, Zeliha Candan (My University, 2021)
Objective: This study aims to determine the effects ofbody percussion (BP) on balance and coordination in elderly people. Material and Methods: We analyzed fifty participants by randomly assigning them to intervention and control groups. The intervention group hadpercussion work for 3 days per week, whereas the control group did notparticipate in percussion. The groups’ static balance was evaluated withRomberg, Single Leg Stance Test, and Functional Reach, while the evaluation of dynamic balance was based on 360° Turn Test and Four StepSquare Test. Lastly, the Berg Balance Scale was used to measure the functional balance, along with the ruler drop test for reaction time. Multiplemeasures such as finger to nose, supination-pronation, knee heel, LowerExtremity Motor Coordination Test, and Soda Pop Coordination Testwere used to demonstrate the effects on the coordination. The first measurements were made at the beginning of the study, followed by the comparison measurements at the 8th week. Results: The results pointed outthat significant intra-group differences were found in the interventiongroup in terms of the Single Leg Stance Test and the Functional ReachTest (p=0.013 and p=0.000), as well as 360° Turn Test and the FourSquare Step Test (p=0.000 and p=0.000). The outcomes of the finger tonose (p=0.032), supination-pronation (p=0.020), and Lower ExtremityMotor Coordination (p=0.003) tests significantly improved in the intervention group. Conclusion: The results demonstrated that BP significantly affects coordination and balance in elderly people. BP haspromising effects as a physical activity for the elderly.

Amaç: Bu çalışmanın amacı, yaşlılarda beden perküsyonunun (BP) denge ve koordinasyon üzerine etkilerini belirlemektir. Gereç ve Yöntemler: 50 katılımcı, çalışma ve kontrol grubu olarak 2’ye ayrılmıştır. Çalışma grubunda, haftada 3 gün perküsyon çalışması yapılırken, kontrol grubu perküsyona katılmamıştır. Romberg Testi, Tek Ayak Duruş Testi ve Fonksiyonel Uzanma Testi ile statik denge; 360° Dönme Testi, Dört Kare Adım Testi ile dinamik denge değerlendirilmiştir. Aynı zamanda, fonksiyonel denge için Berg Denge Ölçeği kullanılmıştır. Reaksiyon zamanı, cetvel düşme testi ile değerlendirilmiştir. Koordinasyon ise parmak burun, supinasyon pronasyon, diz topuk, Alt Ekstremite Motor Koordinasyon Testi, Soda Pop Koordinasyon Testi ile değerlendirilmiştir. Gruplara ilk ölçüm yapıldıktan 8 hafta sonra 2. ölçüm uygulanmıştır. Bulgular: Çalışma grubunda, Tek Ayak Duruş Testi ve Fonksiyonel Uzanma Testi (p=0,013 ve p=0,000) ile 360° Dönme Testi ve Dört Kare Adım Testi (p=0,000 ve p=0,000) açısından anlamlı grup içi farklılıklar bulundu. Çalışma grubunda parmak burun (p=0,032), supinasyon-pronasyon (p=0,020) ve Alt Ekstremite Motor Koordinasyon (p=0,003) testlerinin sonuçları, anlamlı iyileşme gösterdi. Sonuç: Sonuçlar, BP’nin yaşlı insanlarda koordinasyonu ve dengeyi önemli ölçüde etkilediğini gösterdi. BP’nin, fiziksel bir aktivite olarak kullanımı yaşlılar için etkili olabilir.
Yaşlılarda beden perküsyonunun denge ve koordinasyon üzerine etkisi
Keywords: Coordination Complexes; Exercise; Frail Elderly; Percussion; Postural Balance; Koordinasyon Kompleksleri; Egzersiz Yapmak; Kırılgan Yaşlılar; Perküsyon; Postüral Denge